Analisis Dampak Ketimpangan Pendapatan terhadap Kemampuan (Ability to pay) dan Kemauan (willingness to pay) Masyarakat Membayar Iuran Kesehatan atau Pembelian Rokok - Islamiah, Nurhidayati; Suwardi, Wisda Zulaeha (STIM-LPI Makassar, 2024)
Income inequality is based on the inability of several community groups as measured by the average costs incurred by all household members, both for purchasing goods, using services and other payments, with differences in income generated by the community, so this is what drives inequality in income. When consuming goods, people will set aside their income for purchasing or payment purposes. If people's income is low, their ability to pay for consumption and payment of public health contributions tends to decrease, but in terms of purchasing cigarettes, people's willingness to pay tends to remain the same. Several factors that influence this are people's habitual patterns in consuming cigarettes and considering cigarettes as a basic need.This research aims to analyze the influence of income level on people's ability and willingness to pay health fees or purchase cigarettes. This research is a quantitative study with a cross sectional design. The sample collection technique uses simple random sampling, namely sampling of population members is carried out randomly without paying attention to the strata in the population. The samples chosen in the research as respondents were people who were independent BPJS Health participants in the Biringkanaya sub-district. This research was carried out by distributing questionnaires. The data processing technique uses linear regression which is processed using SPSS software. The results of this study explain that there is a relationship between the ability and desire to pay health fees and purchase cigarettes. And this research also explains that income inequality in society has a negative effect on purchasing cigarettes and also paying health fees. It is hoped that this research can be used as a consideration for policies that influence the payment of health fees and the purchase of cigarettes on people's income.